First baseline assessment of seafloor litter on Italian coralligenous assemblages (Mediterranean Sea) in accordance with the European Marine Strategy Framework Directive. (February 2023) - Angiolillo, Michela; Fortibuoni, Tomaso; Di Lorenzo, Bianca; Tunesi, Leonardo
Abstract: A monitoring programme for coralligenous assemblages was carried out in Italy for implementation of the Marine Strategy Framework Directive (MSFD), aiming to characterise the coralligenous' environmental status and litter distribution. A standardised monitoring protocol, based on ROV-imaging, has been applied; this paper analyses the data obtained during the first MSFD cycle (2015–2019). Ninety-five areas were monitored at depths ranging between 14 and 199 m in the three subregions bordering Italy. Overall, 4316 macrolitter items were recorded. The median litter density was 2 items 100 m −2 (range: 0–120 items 100 m −2 ), but significant subregional differences emerged in litter quantities and composition. Fishery-related litter (mainly lines and ropes) was the most common type (86 %), affecting vulnerable coralligenous reefs. A first baseline is proposed for assessing achievement toward Good Environmental Status and evaluation of the efficacy of the Italian MSFD measures aiming to eliminate the negative effects of marine litter on vulnerable reefs. Highlights: Seafloor litter along coralligenous reefs was monitored in Italy by ROV-imaging. Monitoring has been applied since 2015 under Marine Strategy Framework Directive. Ninety-five areas at depths ranging between 14 and 199 m were monitored. 4316 macrolitter items and 2 items 100 m −2 median litter density were recorded. The information collected will be used as baseline for future monitoring cycles.